Peran Mediasi Dalam Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama Pekanbaru - Susilawati Susilawati; Eryana Eryana; Amalia Kartika; Mhd Syamsul Arifin; Sapik Sandra (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
As is known that mediation is the involvement of an independent third party in providing mediation facilities. By negotiating between the two parties assisted by a neutral third party. It has become a principle in civil law that the court is obliged to reconcile the case. This principle also requires the court (Judge) so that when handling a submitted case, the first thing is an effort to reconcile the two parties in the case. The importance of mediation in this context is interpreted not only as an effort to minimize cases that enter the Court, but more than that, mediation can be understood and translated regarding the dispute resolution process as a whole with full sincerity and justice and understanding and also neutral to end an ongoing dispute. So that each party feels fair and can be understood. As stated in PERMA Number 1 of 2016 concerning mediation procedures in Court. Islam is a peaceful religion, which in the Religious Court the majority of people are Muslims, the opportunity for reconciliation is greater. With the aim of reconciling through an agreement produced together without any party taking sides, meaning there is only a neutral party who guides the disputing parties.